1963
DOI: 10.1530/acta.0.0420061
|View full text |Cite
|
Sign up to set email alerts
|

QUANTITATIVE ESTIMATION OF ADRENOCORTICAL HORMONES AND THEIR Α-Ketolic METABOLITES IN URINE

Abstract: Urinary corticosteroid patterns were estimated before and after adrenocortical stimulation by exogenous corticotrophin (ACTH). The results indicate that changes in corticosteroid biosynthesis and metabolism depend on the duration of stimulation. Immediate effects are an increase in corticosterone production above that of cortisol (low F/B-ratio) and a shift in the metabolism of both cortisol and corticosterone in favour of all 11-hydroxycompounds. Late effects are characteristic of the patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1965
1965
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A training set of 7 type 1 and 27 type 2 cases is available, each case, for our limited illustration, having a two dimensional feature vector, consisting of urinary excretion rates of two steroid metabolites, allo-tetrahydrocortisol and tetrahydrocortisone, determined by the paper chromatography method of Cost & Vegter (1962), who state that their method has a 20% coefficient of variation. To take account of a coefficient of variation equal to c the error model (3.3) takes the form…”
Section: Applications 4 1 Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…A training set of 7 type 1 and 27 type 2 cases is available, each case, for our limited illustration, having a two dimensional feature vector, consisting of urinary excretion rates of two steroid metabolites, allo-tetrahydrocortisol and tetrahydrocortisone, determined by the paper chromatography method of Cost & Vegter (1962), who state that their method has a 20% coefficient of variation. To take account of a coefficient of variation equal to c the error model (3.3) takes the form…”
Section: Applications 4 1 Preliminariesmentioning
confidence: 99%
“…The recorded features or measurements of cases arising in statistical diagnostic problems are often imprecise for a variety of reasons, such as physiological variability (Ferriss et at., 1970), assessment by assay techniques (Cost & Vegter, 1962), calibration between sources such as different clinics (Aitchison, 1977) and subjective measurement or observer error (Buckton et at., 1976;Smyllie, Blendis & Armitage, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…The androgen excretion was not investigated. Cost (1963) reported a relatively greater reduction in the excretion of corticosterone metabolites than of cortisol metabolites in 4 out of 6 adults with untreated Addison's disease, and he suggested that this was because endogenous ACTH stimulated the cortisol pathway preferentially. He did not comment on the excretion of androgens in his patients.…”
Section: Pathologymentioning
confidence: 99%
“…Urinary C21-corticosteroid patterns were investigated in the 3 patients using a method described by Cost and Vegter (1962). No aldosterone was detectable in the urine of the 3 patients or in the 2 infants after administration of ACTH and under conditions of hyponatraemia and dehydration.…”
Section: H K a Vissermentioning
confidence: 99%